2015
DOI: 10.1134/s1070428015050164
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new spiro compounds proceeding from 11H-Indeno[1,2-b]quinoxalin-2-one

Abstract: Reaction of 11Н-indeno[1,2-b]quinoxalin-2-one with semi(thiosemi)carbazides in ethanol resulted in semi(thiosemi)carbazones which at boiling in acetic anhydride underwent cylization yielding N-{3'-acetyl-3'Н-spiro[indeno[1,2-b]quinoxalin-11,2'-[1,3,4]oxa(thia)diazol]-5'-yl}acetamides. Aldol crotonic condensation of 11Н-indeno[1,2-b]quinoxalin-2-one with methyl N-(4-acetylphenyl)carbamate afforded the corresponding chalcone that at boiling in anhydrous ethanol with hydrazine hydrate for 1 h formed a spiro compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Later on, this reaction was studied by Velikorodov et al 59 The regioselectivity of the process is very interesting and depends upon the nature of substituents present on the aromatic ring of dipolarophile molecule 41. The threecomponent reaction of dinitriles 41 with an unsubstituted benzene ring or electron-withdrawing substituents (Cl, NO 2 ), Lproline 16d and quinoxalinones 3 (X ¼ CH, N) produced spiropyrrolizidines 42 (56-86% yields) with unexpected regioselectivity.…”
Section: Synthesis Of Spiro-pyrrolidine/pyrrolizine/ Pyrrolothiazole-indenoquinoxalinesmentioning
confidence: 99%
“…Later on, this reaction was studied by Velikorodov et al 59 The regioselectivity of the process is very interesting and depends upon the nature of substituents present on the aromatic ring of dipolarophile molecule 41. The threecomponent reaction of dinitriles 41 with an unsubstituted benzene ring or electron-withdrawing substituents (Cl, NO 2 ), Lproline 16d and quinoxalinones 3 (X ¼ CH, N) produced spiropyrrolizidines 42 (56-86% yields) with unexpected regioselectivity.…”
Section: Synthesis Of Spiro-pyrrolidine/pyrrolizine/ Pyrrolothiazole-indenoquinoxalinesmentioning
confidence: 99%
“…[271] An easily obtainable from indenoquinoxalin-2-one 281 semi-or (thiosemi)carbazones 290 at boiling in acetic anhydride underwent cyclization yielding spiro indenoquinoxalines 291 (Scheme 76). [282]…”
Section: The Strategy Of Direct Spirocycle Buildup To Molecule Of Indmentioning
confidence: 99%
“…Meanwhile, Yang et al [2] discussed the efficient regioselective synthesis of novel functionalized dispiropyrrolidines via a three-component (3 + 2) cycloaddition reaction with a yield of approximately 87%. Additionally, other studies have shown a desired synthetic route for Spiro indeno [1,2-b]quinoxaline-11,3 -pyrrolizidine derivatives [8]. These various approaches were considered for the higher yield of the final compounds including multicomponent derivatives of the heterocyclic Spiro compounds.…”
Section: Introductionmentioning
confidence: 99%